Statebuilding in fragile countries: What can we learn from past stateness? - Andrea Vaccaro; Rachel M. Gisselquist (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Supporting state capacity is a priority for the international community, yet the record of internationally supported statebuilding to date has been mixed at best. A key question for continuing research concerns the factors influencing more versus less successful interventions. We show that the quality of past 'stateness' is crucial in understanding contemporary state fragility and statebuilding. Extending beyond previous work, we introduce the concept of past stateness, consider theoretically its relationship to contemporary fragility, and explore this relationship empirically, drawing on cross-national data and newly developed indicators. In line with our expectations, descriptive and inferential analysis shows that lack of experience of two core features of stateness-monopoly of violence and existence of a professional bureaucracy-in the past century predicts chronic fragility today. This association is mainly driven by monopoly of violence rather than existence of a professional bureaucracy. Our analysis sheds new light on the underlying heterogeneity among states today labelled as 'fragile'. From a policy perspective, a key implication is that, in designing interventions, the most relevant experiences are likely to be from other countries with similar stateness legacies, rather than from 'fragile states' more generally. Our analysis does not imply that statebuilding is impossible in contexts with weak stateness legacies, but it does underscore the challenges of this and the importance of setting expectations appropriately.
Keywords: F50; H10; H70; O57; 330; state fragility; statebuilding; stateness; monopoly of violence; professional bureaucracy